2021
DOI: 10.2147/ijn.s282489
|View full text |Cite
|
Sign up to set email alerts
|

p53 Promoted Ferroptosis in Ovarian Cancer Cells Treated with Human Serum Incubated-Superparamagnetic Iron Oxides

Abstract: In this study, we used MTT assays to demonstrate that a combination of SPIO-Serum and wild-type p53 overexpression can reduce ovarian cancer cell viability in vitro. Prussian blue staining and iron assays were used to determine changes in intracellular iron concentration following SPIO-Serum treatment. TEM was used to evaluate any mitochondrial damage induced by SPIO-Serum treatment, and Western blot was used to evaluate the expression of the iron transporter and lipid peroxidation regulator proteins. JC-1 was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
43
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(43 citation statements)
references
References 42 publications
(33 reference statements)
0
43
0
Order By: Relevance
“…In addition, p53-mediated ferroptosis contributes to the effects of metal-based drugs. For example, overexpression of p53 significantly promotes ferroptosis induced by superparamagnetic iron oxides (SPIO) in ovarian cancer cells, then inhibiting the growth of ovarian cancer ( Zhang Y. et al, 2021 ). p53 mutation is associated with the clinical stage and progression of ovarian cancer.…”
Section: Ferroptosis In Gynecological Malignanciesmentioning
confidence: 99%
“…In addition, p53-mediated ferroptosis contributes to the effects of metal-based drugs. For example, overexpression of p53 significantly promotes ferroptosis induced by superparamagnetic iron oxides (SPIO) in ovarian cancer cells, then inhibiting the growth of ovarian cancer ( Zhang Y. et al, 2021 ). p53 mutation is associated with the clinical stage and progression of ovarian cancer.…”
Section: Ferroptosis In Gynecological Malignanciesmentioning
confidence: 99%
“…In a study by Yamada et al (58), following treatment of the normal ovarian cell line OSE/E7/human telomerase reverse transcriptase (hTERT) genome with iron ions, the genome showed the characteristics of ovarian cancer, and normal ovarian cells gradually transformed into cancer cells. Lidocaine can also promote ferroptosis in ovarian cancer by targeting the miR-382-5p/SLC7A11 axis (59), as does superparamagnetic iron oxide cultured in human serum by regulating p53 (60). Additionally, as being a well-tolerated anti-malarial drug, artesunate can also promote ROS and iron-dependent cell death in ovarian cancer cells, but this process can be prevented by the ferroptosis inhibitor F-1 (61).…”
Section: Ovarian Cancermentioning
confidence: 99%
“…After NPs are degraded into iron ions in lysosomes, iron ions induce oxidative stress by generating ROS [31]. Ferroptosis is a type of ROS-dependent regulated cell death [31], mitochondrial damage is the most common feature of this process which caused by intracellular ROS [18]. As determined by flow cytometry (FCM) (Fig.…”
Section: Mitochondrial Damage Triggered By Fe3o4 Npsmentioning
confidence: 99%
“…Ferroptosis induction is associated with multiple diseases and has recently gained substantial attention as a target for cancer treatment [14]. It is reported that iron oxide NPs induced ferroptosis in few cancer cells [17,18] and ischemic cardiomyocytes [19].…”
mentioning
confidence: 99%